Design of Inverter with Less Harmonics using Buck-Boost Converter and SPWM Method - Lalu Riza Aliyan; Rini Nur Hasanah; M. Aziz Muslim (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In a power distribution system it is expected that the current and voltage values to be maintained constant both in terms of magnitude and frequency. However, distortion of waveforms as a result of non-linear loads connected to system is widely found in a form of harmonics. Harmonics are sinusoidal signals whose frequencies multiples of the fundamental frequency. The severity of harmonics content is commonly stated using Total Harmonics Distortion (THD), revealing the ratio of the Root Mean Square (RMS) values of all harmonic components to its fundamental component, and is expressed in percentage (%). The harmonics could engender undesired effects in some appliances. In this paper, an effort to minimize the THD value in an inverter design is described. Less harmonics were obtained using Buck-Boost Converter and Sinusoidal Pulse Width Modulation (SPWM) Method. Analysis results showed a THD reduction of 4.58 % and 4.33 % for current and voltage respectively.